2018
DOI: 10.1002/lary.27641
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular flap practice patterns and outcomes: A survey of 221 AHNS surgeons

Abstract: Objectives To describe American Head and Neck Society (AHNS) surgeon supraclavicular flap (SCF) practice patterns and to identify variables associated with SCF complications. Methods The design is a cross‐sectional study. An online survey was distributed to 782 AHNS surgeons between November 11, 2016, and December 31, 2016. The primary outcome was frequency of SCF complications. Independent variables included demographics, training, practice patterns, and SCF techniques. Results Adequate survey responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Cervicofacial flaps and SCAIF have a 9% 17 and 18% 18 risk of partial necrosis respectively. A recent survey capturing 221 head and neck surgeons revealed that the rate of complications with SCAIF was 29.8% 19 . In our series when using SCAIF we experienced only one distal tip necrosis (16,6%), and no complications were reported when using cervicofacial flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Cervicofacial flaps and SCAIF have a 9% 17 and 18% 18 risk of partial necrosis respectively. A recent survey capturing 221 head and neck surgeons revealed that the rate of complications with SCAIF was 29.8% 19 . In our series when using SCAIF we experienced only one distal tip necrosis (16,6%), and no complications were reported when using cervicofacial flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Prior survey studies assessing practice patterns regarding malnutrition screening demonstrate response rates ranging from 5.7% 19 to 72%, 16 with recent AHNS surveys reporting response rates of 28%. 22,23 To a certain extent, the low response rate may be explained by fatigue bias, which can occur when surveys are lengthy and/or the participant loses interest toward the end of the survey. 24 This can result in the participant skipping questions or marking responses in a random fashion.…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified higher rates of partial flap necrosis, flap dehiscence, fistula, and donor site dehiscence in comparison to non-SCF flap alternatives in mucosal sites [12 ▪ ]. A cross sectional survey of American Head and Neck Society surgeons revealed limited use of SCF with only 31% of surgeons utilizing the flap for oral cavity reconstructions [13]. This reconstruction may have limited value in oral tongue reconstruction.…”
Section: Supraclavicular Artery Flapmentioning
confidence: 99%